Hemostasis in acute myeloid leukemia patients during disease manifestation - S. G. Vladimirova (Onkogematologiâ, 2014)
The aim of the study was assessment of blood coagulation parameters in acute myeloid leukemia (AML) patients during disease manifestation.Coagulation and fibrinolysis parameters, physiological anticoagulants levels and intravascular coagulation markers were detected. 44 patients with newly diagnosed AML (FAB: M0, M1, M2, M4, M5), m/f = 20/24, aged 20–76 years (median – 49.5 years) were included in the study. 18 patients without infectious complications were classified as a group 1; 26 patients with infectious complication – as a group 2. Hemorrhages were observed in 15 patients (57.7 %) from group 2 and only in 2 patients (11 %) from group 1. The patients showed elevated levels of soluble fibrin monomer complexes and D-dimer levels, decreased protein C activity, inhibition of Hageman-dependent fibrinolysis, which indicates the hypercoagulation. Infection in AML patients accompanied by increased intravascular coagulation that confirmed by positive correlation of CRP with D-dimer levels and von Willebrand factor antigen (VWF:Ag) and by negative correlation with prothrombin tests results. Thus, infection and high leucocytes count in patients with newly diagnosed AML should be considered as significant risk factors for thrombohemorrhagic complications as well as thrombocytopenia.